2022
DOI: 10.3390/vaccines10101770
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Herpes Zoster (Shingles) Catch-Up Campaign at the Romagna Local Health Authority (Italy), a Multi-Center Retrospective Observational Study

Abstract: Herpes Zoster (shingles) is an infection that occurs when varicella-zoster virus reactivates from the latent state. Incidence and severity of Herpes Zoster disease increase with age. Antiviral drugs are the elective treatment; however, prevention of disease reactivation through effective and safe vaccines is available in Italy out-of-pocket from age 65 onwards. The Romagna Local Health Authority (northern Italy) administered catch-up vaccinations in March–May 2022 for immunizations not performed during the COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Aggregate data concerning the uptake achieved during the 2022 catch-up campaign were obtained from a previous research effort conducted by the research team [ 21 ]. Additionally, aggregated data (by cohort and gender) concerning the overall coverage rates achieved for each cohort across all four centers in 2022 and the early months of 2023 were extracted from the vaccination registry of the Romagna LHA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggregate data concerning the uptake achieved during the 2022 catch-up campaign were obtained from a previous research effort conducted by the research team [ 21 ]. Additionally, aggregated data (by cohort and gender) concerning the overall coverage rates achieved for each cohort across all four centers in 2022 and the early months of 2023 were extracted from the vaccination registry of the Romagna LHA.…”
Section: Methodsmentioning
confidence: 99%
“…Aligned with the national vaccination program, the Romagna Local Health Authority (LHA) conducts an annual HZ vaccination campaign specifically targeting individuals who are turning 65 in the respective year and have not previously received the vaccine. During 2022, a catch-up campaign, which concentrated on cohorts born in 1955, 1956, and 1957, was carried out due to missed calls during the COVID-19 pandemic, achieving in the Romagna LHA an adherence rate of 11.4–12.4% [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The recent rise in cases brings attention to the importance of managing the low vaccination rate, which is attributed to public beliefs and perceptions toward HZ and its vaccination [ 8 ]. Despite the fact that vaccination of HZ is available as a preventive measure for shingles, the vaccination rate in Saudi Arabia is still low, reaching around 5% of the target population [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that the reasons for vaccine hesitancy include insufficient information about the diseases, uncertainty about the safety and efficacy of the vaccine, and other cultural factors [ 8 ]. A few studies have suggested a limited awareness of HZ and its vaccination among the Saudi population.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these results, the Advisory Committee on Immunization Practices USA recommends RZV, rather than LZV, in patients with diabetes older than 50 years [ 26 ]. RZV is also being increasingly recommended in national vaccination guidelines across Europe and Canada [ 27 – 29 ].Nevertheless, HZ vaccine coverage is still suboptimal, likely due not only to logistic and economic difficulties [ 30 ], but also to the lack of physician recommendations [ 31 ], although some virtuous experiences have been reported [ 32 ].…”
Section: Introductionmentioning
confidence: 99%